2024
DOI: 10.1007/s00018-023-05092-0
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal modulation of nitric oxide and Notch signaling by hemodynamic-responsive Trpv4 is essential for ventricle regeneration

Chunxiao Yu,
Xueyu Li,
Jinmin Ma
et al.

Abstract: Zebrafish have a remarkable ability to regenerate injured hearts. Altered hemodynamic forces after larval ventricle ablation activate the endocardial Klf2a-Notch signaling cascade to direct zebrafish cardiac regeneration. However, how the heart perceives blood flow changes and initiates signaling pathways promoting regeneration is not fully understood. The present study demonstrated that the mechanosensitive channel Trpv4 sensed the altered hemodynamic forces in injured hearts and its expression was regulated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…Previous studies demonstrated that Csrp3 played an essential role in the CM stretch sensor machinery [ 2 ], and was required for mechanical stability in skeletal muscles [ 27 ]. We recently showed mechanotransduction is critical for zebrafish heart regeneration [ 28 ]. Thus, we also assessed the expression of several genes involved in mechanotransduction process in ablated 218A larval hearts.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies demonstrated that Csrp3 played an essential role in the CM stretch sensor machinery [ 2 ], and was required for mechanical stability in skeletal muscles [ 27 ]. We recently showed mechanotransduction is critical for zebrafish heart regeneration [ 28 ]. Thus, we also assessed the expression of several genes involved in mechanotransduction process in ablated 218A larval hearts.…”
Section: Resultsmentioning
confidence: 99%